ANALISIS DAN PERBANDINGAN WIRELESS DISTRIBUTION SYSTEM (WDS) DAN NON WIRELESS DISTRIBUTION SYSTEM (NON WDS) BERBASIS OPENWRT MENGGUNAKAN ACCESS POINT PADA JURUSAN TEKNIK INFORMATIKA FAKULTAS TEKNIK UNIVERSITAS HALU OLEO - Wahyuddin Aluddin; LM Fid Aksara; Jumadil Nangi (Informatics Engineering Department of Halu Oleo University, 2018)
The wireless network is one of the best alternatives in building a network of computers that is practical, in some agencies and the commercial wireless network is used to support an existing wired network. But its implementation is still used cable network that became the backbone of the access point so that a client that is connected can access the internet. Wiring problems can be a considerable obstacle in places that are hard to reach.The wireless distribution system is a system for developing a wireless internet network without having to use a cable as a backbone for the access point but instead of utilize a wireless line of the access point. At the time of the wireless distribution system network, topology and network topology of the non-wireless distribution system is applied, will be on analysis using Wireshark, the QoS parameter application that consists of a Delay, Throughput, and Packet Loss.The testing performed against the clients who are numbered six (6) is each connected to the access point. Scenario testing is done i.e. the conditions streaming and download, made during the three (3) days. Of test results obtained, the wireless distribution system network topology has the value throughput, delay; packet loss is a little less useful than a non-network topology wireless distribution system. But the differences in the average value of the QoS parameters that are generated are not too significant.Keywords—Wireless Distribution System, Non-Wireless Distribution System, Quality of Service (QoS)